The Decision of The Constitutional Court on Verification of Political Parties - Yusuf Mulya Kharismawan; Yulia Neta; Muhtadi Muhtadi (Fakultas Hukum Universitas Lampung, 2023)
Political parties are the political suprastructure in a democratic country as a means for citizens to occupy political positions through general elections. The requirements for verifying political parties participating in an election are always contained in every election law making it difficult for political parties to pass verification as well as excluding several political parties that have met certain verification requirements so that they are immediately declared as participants in the next elections. This exception is not in accordance with several Constitutional Court Decisions which have the same substance which consistently declares unconstitutional, except for the Constitutional Court Decision Number 55/PUU-XVIII/2020. The research method used is normative juridical regarding laws and regulations, namely Law Number 7 of 2017 concerning Elections, accompanied by comparative study of jurisprudence Constitutional Court's decision regarding an application for judicial review of political party verification accompanied by literature studies. The research analysis uses a qualitative approach to understand more deeply the legal phenomena that occur and examines the substance to obtain specific conclusions on what is studied. That decision based on a discussion of this research is inconsistent because the arguments and materials of the 1945 Constitution used are different and the Constitutional Court is not required to use jurisprudence as a basis for consideration even though there are similarities in substance.